Oxysterol concentrations are associated with cholesterol concentrations and anemia in pediatric patients with sickle cell disease. (18th August 2019) - Yalcinkaya, Ahmet; Samadi, Afshin; Lay, Incilay; Unal, Selma; Sabuncuoglu, Suna; Oztas, Yesim
Abstract: Sickle cell disease (SCD) causes anemia, oxidative stress, chronic inflammation, and lipid abnormalities. Oxysterols are oxidized derivatives of cholesterol and affect cholesterol metabolism and eryptosis. Our aim was to determine whether the plasma concentrations of 7-ketocholesterol (7-KC) and cholestane-3β, 5α, 6β-triol (C-triol) were associated with hemolysis and lipid profile in patients with SCD. A total of 32 steady-state pediatric patients with SCD (22 HbSS and 10 HbSß + ) and 25 healthy controls were included in the study. Hemolysis parameters, ferritin, serum iron, lipids, 7-KC and C-triol concentrations of all subjects were measured. Oxysterols were quantified with N, N-dimethylglycine derivatization via LC-MS/MS. 7-KC and C-triol concentrations were found to be increased in SCD patients, while there was no difference between the HbSS and HbSß + subgroups. 7-KC concentrations s were correlated negatively with hemoglobin and positively with lactate dehydrogenase concentrations, while C-triol concentrations were negatively correlated with HDL cholesterol. Furthermore, while 7-KC and C-triol concentrations were highly correlated among controls, there was no correlation in patients. The findings of our study suggest that 7-KC and C-triol may have a role in SCD pathophysiology. The lack of correlation in patients' 7-KC and C-triol concentrations suggest alterations in oxysterol production in patients with SCD.